2014
DOI: 10.1080/07481187.2014.907089
|View full text |Cite
|
Sign up to set email alerts
|

The Grief and Meaning Reconstruction Inventory (GMRI): Initial Validation of a New Measure

Abstract: Although increasing numbers of grief theorists, researchers, and therapists have begun to focus on the quest for meaning in lives disrupted by loss, no convenient and psychometrically validated measure of meanings made specifically in bereavement has been available to guide their efforts. To construct such a measure, the authors began with a systematic content analysis of sense-making, benefit finding, and identity reconstruction themes gleaned from the narrative responses of a sample of 162 adults who were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 45 publications
4
43
0
4
Order By: Relevance
“…Consistent with previous research (Gillies et al, 2015) each factor of the GMRI demonstrated a significant, weak to moderately strong correlation with every other GMRI factor and with the total GMRI score. This finding is in line with the conceptualization of each GMRI factor as representative of a distinct theme of meaning made following loss.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous research (Gillies et al, 2015) each factor of the GMRI demonstrated a significant, weak to moderately strong correlation with every other GMRI factor and with the total GMRI score. This finding is in line with the conceptualization of each GMRI factor as representative of a distinct theme of meaning made following loss.…”
Section: Resultssupporting
confidence: 91%
“…The GMRI (Gillies et al, 2015) is a 29-item, Likert-type (1 = Strongly Disagree to 5 = Strongly Agree), self-report measure which was developed with a bereaved sample and contains five factors each reflecting a theme of meaning made: Emptiness and Meaninglessness (e.g. ‘I feel empty and lost’), Personal Growth (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary 'best fit' analysis of existing validated measures used during the initial outcome mapping process found no tools that completely covered these dimensions but identified some with apparent potential to be combined or adapted to cover the outcomes. Those with 'best fit' included grief specific measures connected with coping, resilience and meaning based frameworks, such as the Inventory for Daily Widowed Life [26], Adult Attitude to Grief Scale [27], Grief and Meaning Reconstruction Inventory [28]. There were also some generic quality of life and wellbeing tools which demonstrated good coverage of the selected quality of life and wellbeing dimensions e.g.…”
Section: Limitations Strengths and Implications For Further Researchmentioning
confidence: 99%
“…In the former case, the griever's bond with the deceased represents meaning made of the loss whereas in the latter case meaning made manifests as valuing life. Gillies, Neimeyer, and Milman () carried out a thematic analysis of bereavement narratives in an attempt to capture this variety in the content of meaning. The meaning themes that emerged informed the items of the Grief and Meaning Reconstruction Inventory ( GMRI ; e.g., “I value and appreciate life more”; Gillies et al, ).…”
Section: Introductionmentioning
confidence: 99%